The Effect of “Kupas Rangkai” towards Reading Skill for Intellectual Disability Students of Grade IV in Special School - Janatu Rojiati; M Shodiq AM (Journal of ICSAR, 2017)
Rading has important position in learning proces, one of them student will be able to master various field studies. The subjects of this research have difficulties in basic reading. The purpose of this study was to know the effect of ‘Kupas Rangkai’ method towards reading skills for intellectual disability students of grade IV in Special School. The method was pre experiment with one group pretest-posttest design. Revenue in this research increased by 11 percen. So means there were differences of reading skill of intellectual disability students of grade IV before and after given treatment ‘Kupas Rangkai’ method. The suggestion for the teacher is make learning more creative and innovative